International convention tourism: A choice modelling experiment of host city competition. (April 2019) - Crouch, Geoffrey I.; Del Chiappa, Giacomo; Perdue, Richard R.
Abstract: Many cities around the world today place considerable emphasis in their tourism strategies on enhancing their competitiveness as potential convention hosts. The objective of this research was to evaluate how site attributes affect the choice of a host city in the international conventions tourism market. The study employed discrete choice modelling using a stated choice approach and analysed data from a survey of international association convention planners. The results demonstrated that the top ten site attributes were (in descending order): the convenience of flight schedules; risk of disruption to the convention; inbound travel barriers or formalities; on-site vs. off-site delegate accommodation; number of available four star hotels; cost of the convention facility; possibility of a subsidy to defray costs; number of available five star hotels; whether or not the association held its convention at the site previously; and domestic air travel costs. Highlights: Convention centre facilities are important but not paramount. Accessibility of a city in terms of flight schedule convenience is a major consideration. The risk of a potentially disrupted convention is also influential. The quality and range of accommodation alternatives is a high priority. Subsidies and local chapter support are also often significant factors.